Coxsackievirus B: The important agent of hand, foot, and mouth disease. Issue 3 (20th March 2023) - Liu, Yuhan; Chen, Junwei; Zhang, Ming; Guo, Wei; Feng, Changzeng; Liu, Jiansheng; Xu, Lilan; Gao, Na; Ma, Shaohui
Abstract: Hand, foot, and mouth disease (HFMD) is a common pediatric infectious illness caused by enteroviruses (EVs). EV‐A serotypes are the main pathogens associated with HFMD. In this study, 213 stool samples from 213 children with severe HFMD in Yunnan, China in 2013, 2015, and 2016 were further analyzed retrospectively for EV‐B infection. A total of 70.0% of the specimens tested positive for EV.20 EV serotypes were detected. The predominant serotype was enterovirus A71 (EV‐A71, 27.7%), followed by coxsackievirus B4 (CV‐B4, 16.4%), CV‐A16 (9.9%), CV‐B5 (6.6%), and Echovirus 9 (E‐9, 4.7%). EV‐A and EV‐B accounted for 45.1% and 41.3%, respectively. Among the positive specimens, 28.6% were CV‐Bs. Co‐infection was present in 19.3% of these cases. In the study, CV‐B5 and the majority of CV‐B4 isolates belonged to genotypes VI and C3, respectively. This result indicates that EV‐B, especially CV‐Bs, might be the important agents associated with HFMD and this knowledge will contribute to the prevention and treatment of the disease.